2012
DOI: 10.1093/heapol/czs116
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the National Essential Medicines Policy on prescribing behaviours in primary care facilities in Hubei province of China

Abstract: The NEMP interventions reduced the average cost per prescription; however, the irrational use of antibiotics and unnecessary parenteral administration remains prevalent. The goals of the NEMP are partially achieved; we therefore recommend a strategic approach involving all stakeholders to comprehensively achieve all aspirations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 29 publications
7
95
1
Order By: Relevance
“…However, providers' accounts suggested that financial considerations in different healthcare institutions were not in line with the policies' focus, with evidence that making profits from antibiotic prescriptions was still regarded as a factor related to the use of antibiotics in CHIs. These findings are similar to studies undertaken in various provinces in China, which noted that the EDL and ZMU policies had no effect on the inappropriate use of antibiotics among primary care institutions [52][53][54], even in the period after the introduction of 2011 reform [51,55,56].…”
Section: Discussionsupporting
confidence: 88%
“…However, providers' accounts suggested that financial considerations in different healthcare institutions were not in line with the policies' focus, with evidence that making profits from antibiotic prescriptions was still regarded as a factor related to the use of antibiotics in CHIs. These findings are similar to studies undertaken in various provinces in China, which noted that the EDL and ZMU policies had no effect on the inappropriate use of antibiotics among primary care institutions [52][53][54], even in the period after the introduction of 2011 reform [51,55,56].…”
Section: Discussionsupporting
confidence: 88%
“…Misaligned economic incentive for health providers is the main contributor to the overprescribing of antibiotics in China. Although China has implemented a zero drug profit policy since 2009, which aimed at removing profits on drug sales of health facilities, the connection between drug companies and individual doctors still contributes to this problem [18,19]. Compared with more developed regions, healthcare providers in less developed regions had lower incomes, experienced relaxed regulations, and were more likely to profit from overprescribing antibiotics [7,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…In a quasi-experimental survey analysis of 55,800 prescriptions in primary care facilities in Hubei province, implementation of the EDL decreased the average cost per prescription [from 26.67 RMB to 44.67 RMB ($4.13-$6.93)] but did not reduce either prescription of antibiotics or parenteral drug delivery (79). Although early studies suggest decreases in inpatient spending due to EDL implementation (92), later studies suggest an increase in overall spending.…”
Section: Impact Of Reformsmentioning
confidence: 99%